MEASUREMENT OF ADIPONECTIN IN VITREOUS AND PLASMA OF PATIENTS WITH PROLIFERATIVE DIABETIC RETINOPATHY AND ITS CORRELATION WITH VASCULAR ENDOTHELIAL GROWTH FACTOR, PIGMENT EPITHELIAL DERIVED FACTOR AND INSULIN LIKE GROWTH FACTOR-1. - VIDHYA SRINIVASAN MS; SUBBULAKSHMI CHIDAMBARAM PHD; KARUNAKARAN CORAL PHD; PUKHRAJ RISHI MS; SULOCHANA KN PHD (International Journal of Pharma and Bio Sciences, 2013)
Purpose of this study was to measure adiponectin (APN) and to compare with already known players of retinopathy namely VEGF, PEDF and IGF-1 in vitreous and plasma of patients with PDR. Methods: Plasma and vitreous samples of 26 patients with PDR who underwent vitrectomy were analyzed for APN, PEDF, IGF-1 and VEGF by ELISA. Among these 19 patients were underwent laser treatments prior to vitrectomy. Disease matched control samples were collected from 11 Macular Hole (MH) patients. The study was done with prior approval from Institution Ethics Board. Results: The vitreous samples from PDR patients (n=29) showed increased level of APN (91.1 ng/ml, p<0.0001) when compared to 0.32 ng/ml in vitreous from MH patients (n=11). PDR patients who underwent LASER treatment showed 3 fold increase in vitreous APN (113.5ng/ml, p < 0.03), and a significant decrease in VEGF levels (p < 0.002) than those who had not. Vitreous APN, VEGF and IGF -1 levels were significantly elevated in patients with PDR (p < 0.000) as compared to those with MH. Plasma PEDF was significantly elevated in patients with PDR (p < 0.000) and positively correlated with plasma glucose (p< 0.009). Plasma APN in PDR and whole study group positively correlated with HDL (p < 0.03). Conclusions: Increased vitreous APN and a negative correlation with VEGF after LASER treatment was observed in PDR. Increased PEDF in plasma and its positive correlation with plasma glucose was also seen in PDR group.